The Use of Quizizz: Classroom Action Research on Financial Transaction Materials - Ainiyah, Nur (Journal of Office Administration : Education and Practice, 2023)
In this study, researchers want to prove whether the use of Quizizz and Learning Videos and Zoom Meetings which are equipped with Online Assessments Using Google Form can improve the learning outcomes of Recording Financial Transactions for Students of eleventh-grade Automation and Office Management Program of Vocational High School 1 Surabaya. Research on Financial Transaction Recording is equipped with Online Assessment using Google Form for students in the eleventh-grade Automation and Office Management Program of Vocational High School 1 Surabaya. After applying the use of Quizizz, learning outcomes increased by more than 65% of students have completed learning and the average overall score of students reached more than 65. In each lesson, the researcher explains the learning material using Quizizz and learning video media through Zoom meetings which are equipped with online assessments using Google Form. Various instruments used in this study include learning outcomes test sheets in the form of student respondent questionnaires, pre-tests and post-tests, observation sheets, interview sheets, student response questionnaires, and student worksheets. After the class action research was conducted there was a significant increase. Cycle 1 was 70% and cycle 2 was 94.00%. The average score obtained has increased from cycle 1 of 76 (quite good), and cycle 2 of 87 (good).